Does inchinkoto, a herbal medicine, have hepatoprotective effects in major hepatectomy? A prospective randomized study. Issue 5 (12th January 2015) - Mizutani, Tetsushi; Yokoyama, Yukihiro; Kokuryo, Toshio; Ebata, Tomoki; Igami, Tsuyoshi; Sugawara, Gen; Nagino, Masato
Abstract Objectives This randomized clinical trial was designed to investigate whether inchinkoto has a hepatoprotective effect on postoperative outcome after major hepatectomy. Methods Sixty‐one patients scheduled for major hepatectomy were randomly assigned to one of two groups in which preoperative inchinkoto was (inchinkoto group, n = 30) or was not (non‐inchinkoto group, n = 31) administered. Inchinkoto was administered for at least 7 days before surgery. The primary endpoint was the incidence of post‐hepatectomy liver damage. The expression of nuclear factor E2‐related factor 2 (Nrf2) and other oxygen stress‐related markers in the liver were also determined. Results There was no significant difference in clinical characteristics between the inchinkoto and non‐inchinkoto groups. Serum levels in liver function tests and incidences of post‐hepatectomy liver failure did not differ significantly between the two groups. However, there was a significantly higher induction of antioxidant factors in the liver, such as Nrf2 protein and heme oxygenase‐1 mRNA, after hepatectomy in the inchinkoto group than in the non‐inchinkoto group. Conclusions The preoperative administration of inchinkoto did not have a significant impact on the overall outcome of major hepatectomy. However, inchinkoto induced the expression of Nrf2 during hepatectomy and may have exerted an antioxidative effect on the liver.